Knowledge and attitudes toward COVID-19 vaccination in Sudan: A cross-sectional study - Safaa Badi; Loai Abdelgadir Babiker; Abdullah Yasseen Aldow; Almigdad Badr Aldeen Abas; Mazen Abdelhafiez Eisa; Mohamed Nour Abu-Ali; Wagass Abdelrhman Abdella; Mohamed Elsir Marzouq; Musaab Ahmed; Abubakr Ali M Omer; Mohamed H Ahmed (AIMS Press, 2023)
Background: Vaccines are an essential part of public health interventions to mitigate the devastating health and non-health impacts of COVID-19 pandemic. Despite the fact that Sudan launched the COVID-19 vaccination program in March 2021, only 10% of the population received their two primary doses of vaccines by the end of May 2022. This delayed uptake of vaccines obviously warrants investigation. Therefore, we have conducted this study to evaluate the knowledge, attitude and acceptance of the general population in Sudan toward COVID-19 vaccines. Methodology: A descriptive cross-sectional community-based study. The data were collected using an electronic questionnaire from 403 individuals living in Khartoum, Sudan. The data were processed using the Statistical Package for Social Sciences (SPSS), and data analysis was performed using appropriate tests. Results: 51% of the participants were found to have sufficient knowledge about the COVID-19 vaccine, and the knowledge level is higher among those educated beyond the secondary school and those who were employed. Among those unvaccinated, only 47% of the participants expressed their intention to take the vaccine when offered to them. The major reason for not trusting the vaccine is safety concerns expressed by 65.5% of the unvaccinated. Conclusion: Higher education levels and employment were associated with an increase in sufficient knowledge about the vaccine in around half of the participants. However, most of participants had not taken the vaccine at the time of the study, and the trust in vaccines is not high. Effective interventions by the health authorities are needed to address these issues in order to accelerate the COVID-19 vaccination program in Sudan.